EFFECTIVENESS OF SURGICAL TREATMENT OF KNEE JOINT FLEXOR CONTRACTURE IN CHILDREN'S CEREBRAL PALSY (Herald of the National Children's Medical Center, 2025)
In pediatric cerebral palsy (BTF), the main types of orthopedic pathology in the knee joint are changes in the sagittal plane, the most common of which are bending deformities in the knee joint. In patients with BTF, the development of flexor contracture (TBBK) of the knee joint may also be associated with the weakness of the calf three-headed muscle (BUBM), which is largely a result of stretching beyond the standard of Achilles pain. In this case, the patient tries to correct the heel deformity by bending the knee joint while walking, resulting in a “three-Bevel bend”. The condition is complicated by the significant strength of the muscles of the caviar, which also contributes to the bending of the knee joint. A patient with BTF cannot maintain his balance when moving, contributing to the development of flexor contracture of the knee joint.
Keywords: cerebral palsy; knee joint; flexor contracture; surgery; muscle tone